2020
DOI: 10.9734/csji/2019/v28i430148
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Cashew Nut Shell Liquid and a Commercial Demulsifier for Treating Crude Oil Emulsions

Abstract: Cashew Nut Shell Liquid (CNSL), a natural phenolic liquid extracted from locally sourced raw materials, and Phasetreat-4633 (a commercial demulsifier) were diluted with xylene and butanol and used as demulsifiers in the treatment of crude oil emulsions. Laboratory simulated crude oil emulsions dosed with different concentrations of CNSL and PT-4633 were the basis for comparison of demulsifier performance via the bottle test method. Different factors affecting demulsification efficiency such as; water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It gives 70% of anacardic acid (1), 16% of cardol (2) and 4% of cardanol (3) isolated after precipitation with calcium hydroxide and column chromatography. This is very close to what is described by O. Victor-Oji et al [28]. In some cases, cashew nut shells were collected over 3 years ago and the results turned out to be very similar, which shows the very high stability of this raw material.…”
Section: Products Testedsupporting
confidence: 90%
See 1 more Smart Citation
“…It gives 70% of anacardic acid (1), 16% of cardol (2) and 4% of cardanol (3) isolated after precipitation with calcium hydroxide and column chromatography. This is very close to what is described by O. Victor-Oji et al [28]. In some cases, cashew nut shells were collected over 3 years ago and the results turned out to be very similar, which shows the very high stability of this raw material.…”
Section: Products Testedsupporting
confidence: 90%
“…Foaming Property and Cleaning Powers Foaming property has been tested according to standard (NFT 73-404). This is a static method by Ross-Miles [28]. It involves evaluating the volume of the initial foam and its stability over time.…”
Section: Effect On Viability Of Nhek (Normal Human Epidermal Keratino...mentioning
confidence: 99%
“…The properties of the CNSL extract as determined by Victor-Oji et al [7] showed that the oil extract was dark-brown in colour, with a percentage yield of 35, and specific gravity of 0.87 at 22.5 ℃. The acid, iodine, and saponification values were 1.63, 71.76 and 173.44 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The hot extraction method involves; the roasting process at 300 ℃, hot oil bath process and steam processing at 270 ℃, the CNSL obtained by this method is referred to as Technical CNSL (TCNSL)majorly composed of cardanol, while cold extraction method involves; solvent extraction using acetone, hexane, ethanol, toluene or by a hydraulic press and the CNSL obtained via this method is referred to as Natural CNSL (NCNSL)majorly composed of anacardic acid (as shown in Table 1) [5,6]. NCNSL has been found to be effective as demulsifiers [7] and has also been used in the synthesis of phenolic resins that were effective as pour point depressants (PPDs) in waxy crude oils [8]. The unique chemical properties of CSNL, its availability as a cheap, sustainable and renewable source for naturally occurring substituted phenols and unsaturated phenols, holds promise as an alternative raw material to conventional chemical demulsifiers in the development of novel surfactants for resolving crude oil emulsions [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation